2018
DOI: 10.1371/journal.pntd.0006652
|View full text |Cite
|
Sign up to set email alerts
|

The impact and cost-effectiveness of controlling cholera through the use of oral cholera vaccines in urban Bangladesh: A disease modeling and economic analysis

Abstract: BackgroundCholera remains an important public health problem in major cities in Bangladesh, especially in slum areas. In response to growing interest among local policymakers to control this disease, this study estimated the impact and cost-effectiveness of preventive cholera vaccination over a ten-year period in a high-risk slum population in Dhaka to inform decisions about the use of oral cholera vaccines as a key tool in reducing cholera risk in such populations.Methodology/Principal findingsAssuming use of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 26 publications
1
21
0
Order By: Relevance
“…The costs per case averted during the 2016 OCV campaign were higher and estimated at US$369–US$532 for children ≤15 years old as compared to US$352–US$528 for older patients. This was similar to findings documented by Khan et al, 2018 that showed that varying costs of treatment do not substantially change the resulting ICERs [50].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The costs per case averted during the 2016 OCV campaign were higher and estimated at US$369–US$532 for children ≤15 years old as compared to US$352–US$528 for older patients. This was similar to findings documented by Khan et al, 2018 that showed that varying costs of treatment do not substantially change the resulting ICERs [50].…”
Section: Discussionsupporting
confidence: 91%
“…Based on prescribed guidelines for treating cholera patients of different age groups, this paper considers treatment costs and vaccine effectiveness as key variables for calculating ICERs. Other studies have disregarded vaccine efficacy and demonstrated cost-effectiveness of OCV in endemic settings using cholera incidence and cost of vaccine as key variables [50].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Azithromycin is recommended for pregnant women and young children whereas tetracycline is suitable for adults. They are both more advantageous than ciprofloxacin and erythromycin 1, 11, 12 .…”
Section: Antibiotics/antimicrobialsmentioning
confidence: 99%
“…The endemicity of cholera in Bangladesh is demonstrated by the predictable yearly occurrence of the disease in the country's high-risk districts and the repetitive seasonal pattern of cholera outbreaks, in spring or autumn, or both [4]. Indeed, cholera is increasingly becoming an urban disease, in Bangladesh particularly for Dhaka, the capital city of Bangladesh [5]. Dhaka has also experienced massive cholera outbreaks in the past two decades, especially during major floods in 2007 and 2009.…”
Section: Introductionmentioning
confidence: 99%